Արցախի Տիգրանակերտի անտիկ շրջանի դրոշմազարդ խեցեղենը - Գաբրիելյան, Արմինե (ՀՀ ԳԱԱ Հնագիտության և ազգագրության ինստիտուտ)
Արցախի Տիգրանակերտի անտիկ ժամանակաշրջանի (մ.թ.ա. 1-ին – մ.թ. 3-րդ դդ.) նյութական և հոգևոր մշակույթի ուսումնասիրության առումով մեծ աղբյուրագիտական նշանակություն ունի վերոհիշյալ ժամանակաշրջանի խեցեղենը, որը մեկուկես տասնամյակ տևած պեղումների ամենաառատ հնագիտական նյութն է: Այն, բացի ձևերի բազմազանությունից, ունի նաև մեկ այլ առանձնահատկություն՝ ներկայանում է շքեղ գունազարդ, սև և մոխրագույն, փայլեցված, դրոշմազարդ և փորագիր զարդերով հարդարված տեսակներով: Այս շարքում, թեև փոքրաթիվ, բայց յուրահատուկ խումբ են կազմում դրոշմազարդման եղանակով հարդարված անոթները, որոնք կարող են լույս սփռել Տիգրանակերտի մշակութային նորամուծությունների, առևտրա-մշակութային կապերի և տարածաշրջանում նրա խաղացած մշակութային դերակատարման վրա: The stamped pottery is of a great significance for the research of the material and spiritual culture of the Classical period (I century BC - III century AD) of Tigranakert of Artsakh (the former Nagorno-Karabakh Autonomous region). The ceramic assemblage includes vessels of different forms and styles, as well as elaborately decorated, black and grey polished, stamped and incised examples. The examples, decorated with stamped ornamentation make a small, but diverse group in this collection. Distinctive examples of the stamped pottery discovered during the excavations of Tigranakert at different field seasons are black, polished goblets, phialas and fragments of bowls, decorated with stamped images of grape clusters. The elegant execution of the design of the polished black cluster-bearing vessels, with a dense black slip and surface polishing leave an impression of lacquering. All these characteristics allow suggesting that they were used for a particular purpose. The next group of the stamped pottery of Tigranakert is presented by potsherds with surface color that varies from light reddish-pink to ochre. They bear stamped decorations of a tree or a leaf in different positions. Pottery with different stamped decorations had been widespread in the Armenian highlands since the Urartian period. Only a few examples of stamped pottery are known from sites of the Classical period in Armenia (Artashat, Avan, Yervandashat). In this context, the stamped pottery of Tigranakert is of a great importance. It reveals essential evidence regarding the trade and cultural connections, cultural innovations, and the cultural role Tigranakert played in the region in the Classical period. Для изучения материальной и духовной культуры Арцахского Тигранакерта античного периода (I в. до н.э. - III в. н.э.) большое источниковедческое значение имеет посуда. Керамический ассортимент включает не только сосуды различных форм, но и богато орнаментированные, черные и серые лощеные, штампованные образцы и также сосуды с резной орнаментацией. В этом штампованным методом. Исключительными примерами штампованной керамики являются выявленные благодаря раскопкам Тигранакерта в различные годы черные, лощеные до зеркального блеска кубки, чаши-пиалы и фрагменты мисок, с внутренней стороны украшенные штампованными изображениями гроздей винограда. Изящное исполнение всей композиции чернолощеных сосудов, украшенных изображениями гроздей винограда, черная густая обмазка, лощение, которое оставляет впечатление черной лакировки, придают этим сосудам особую красоту и позволяют предположить, что они использовались в особых целях. Следующую группу сосудов Тигранакерта со штампованным орнаментом составляют фрагменты с оттенками от светло-красно-розового до охристого. На них представлены изображения дерева или листьев, имеющих различное расположение.
Keywords: Հուշարձաններ; Գտածոներ